Exploring the impact of TikTok and Instagram marketing on generation Z cosmetics female consumers in the Czech Republic - Vasylchenko, Olha; Kottika, Efthymia, 1982-; Karlíček, Miroslav, 1979-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
This bachelor's thesis investigates the effects of TikTok and Instagram on female Zoomers' cosmetics purchases in the Czech Republic. As a result, in-depth interviews with young women living in the Czech Republic were done. Data from the in-depth interviews were analyzed using qualitative research techniques. The results imply that video reviews are crucial for female Czech consumers when deciding whether to buy cosmetics. In addition, customers frequently believe less well-known Instagram and TikTok influencers regarding cosmetics brands and have higher level of trust in them, rather than in famous ones with large following base. Finally, because Generation Z female consumers no longer find typical Instagram pop-up advertising compelling, they are primarily impacted by TikTok marketing.
Vedoucí práce: Efthymia Kottika
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses